Emulsification using a "Sonolator" liquid whistle: A new correlation for droplet size from pilot-scale experiments. (2nd November 2018) - Ryan, David J.; Baker, Michael R.; Kowalski, Adam J.; Simmons, Mark J.H.
Highlights: Emulsion drop sizes measured on a pilot – scale liquid whistle device. Three orders of magnitude of dispersed phase viscosity considered. Drop size scales with pressure drop, drop viscosity and surfactant concentration. Expected regime change from turbulent inertial to turbulent viscous not observed. Abstract: Emulsification experiments have been carried out on a pilot-scale Model ACIP2 Sonolator liquid whistle device by examining the change in droplet size distributions of silicone oil in water emulsions, using SLES as a surfactant, before and after processing. The process variables considered were mass flow rate, pressure drop across Sonolator, oil viscosity (from 10 to 10, 000 cSt), oil concentration (0.5–10 wt%), surfactant concentration (0.00003–0.5 wt%) and orifice size. All experiments were carried out in the turbulent flow regime. The oil phase was added as either a pure phase or as a pre-emulsion stabilised using SLES. The oil was injected just before the blade or mixed at a T-junction prior to the Sonolator; the pre-emulsion was exclusively introduced via the latter method. The resultant droplet size distributions were obtained from offline sampling using laser diffraction. The most significant parameters found to influence the drop size were found to be pressure drop, dispersed phase viscosity and surfactant (SLES) concentration, which formed the basis for an empirical power law correlation. Indices in this correlation were compared to findings in the literature for other emulsification devices, and to those predicted from the theories of droplet breakage in turbulent inertial flow. Despite an expected regime change from turbulent inertial to turbulent viscous break-up being common in the literature as the dispersed phase viscosity is increased, this phenomenon was not observed in the experimental data obtained, suggesting breakage in an intermediate regime.